The International Contracting Practices Survey Project: an Empirical Study of the Value and Utility of the United Nations Convention On the International Sale Of Goods (Cisg) and the UNIDROIT Principles of International Commercial Contracts to Practitione - Fitzgerald, Peter L (Journal of Law and Commerce, 2008)
In an era of globalization it is perplexing that so many U.S. practitioners, jurists, and legal academics continue to view contract issues as governed exclusively by state common law and the Uniform Commercial Code. In essence, a significant number of lawyers may be defaulting to the wrong law, in the absence of an effective choice of law clause, when trying to determine the rights and responsibilities arising out of international commercial transactions. The object of the International Commercial Contracting Practices Survey Project was to learn more about how and why this occurs.